Cardiorespiratory resistance profile in elderly women with overweight in SESC of Nova Friburgo/Rio de Janeiro - Brasil of physical activity program - H.L. Furtado; F.D. Pereira; M.H. Moreira; E.H. Dantas (Desafio Singular, 2008)
The study objective was to investigate if one physical activity program promotes significant improvements in the cardiorespiratory capacity in elderly. They had participated of study 71 feminine elderly people, being divided in four groups in the respective age band: : G1 (60-64 years old; n=29), G2 (65-69 years old; n=22), G3 (70-74 years old; n=11) e G4 (75-79 years old; n=09). The cardiorespiratory fitness was evaluated through the 6 minutes walked test (Rikli and Jones 1998). After that, for normality verification had been used the Shapiro-Wilk test, with significance level < 0,05, was used program SPSS 10,0 for Windows. Analyzing the covered distance changeable, one got the following averages: G1 = 526 m, G2 = 509,7m, G3 = 491,3 m and G4 = 479,4 m, can be concluded that the G1 did not only get its value inside of the reference band. Considering the possibility of not the specific of the prescription physical exercise for each age band presented by the studied groups, the physical activity program was capable to provide 60.5% elderly, a satisfactory profile for the cardio-respiratory resistance.